Nonlinear Axisymmetric Deformation Model for Structures of Revolution (Advances in Applied Mathematics and Mechanics, 2011)
An axisymmetric formulation for modeling three-dimensional deformationof structures of revolution is presented. The axisymmetric deformationmodel is described using the cylindrical coordinate system. Largedisplacement effects and material nonlinearities and anisotropy areaccommodated by the formulation. Mathematical derivation of theformulation is given, and an example is presented to demonstratethe capabilities and efficiency of the technique compared to thefull three-dimensional model.